Genuine contribution of Turkish medical institutions to medicine - Onat, Altan (Cerrahpaşa Medical Journal, 2013)
Objectives: To quantitatively evaluate the cumulative genuine contribution over the past 3 decades of Turkey’s institutions to medicine by major fields. Methods: Addresses of over 70 main medical institutions were searched in the Citation Reports section of the Web of Science, and publications that received 60 or more citations by August 2010 were eligible. Papers having more than a minor share by international authors were excluded. Results: Only 33 medical faculties and 6 institutions generated articles that were cited ≥60 times. These publications, 203 in number, received an aggregate of 17,600 citations. Nearly half of these were acquired by Hacettepe, Cerrahpasa and Istanbul Medical Faculties. A total of 156 scientists were unique primary authors, 46 scientists among whom generated over half of the high citations. These findings were estimated to represent roughly 1.4 per mille share of the corresponding global medical citations, and that annually 15-20 such papers are produced in Turkey. Compared with average level of contributions, internal medicine and neurosciences exhibited 1.7-2.0-fold higher contributions, while surgery, basic sciences and pediatrics had half the mean level of impact. Turkey’s global share in highly-cited papers is estimated to have doubled each 12 years. Conclusion: Further to enhancing medical research in general, research having a potentiality to contribute to medicine should specifically to be supported with a coherent and consistent long-term policy.